Diuretic and Antihyperglycemic Potential of Screwpine (Pandanus martellii Elmer) in Female Albino Mice - Agbayani, Ma. Ysalou; Cabauatan, Jane (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the phytochemical constituents, acute oral toxicity, diuretic activity, and antihyperglycemic potential of the roots, fruits, and leaves of Pandanus martellii as a potential plant-based therapeutic agent for diabetes mellitus and hypertension. Anchored on the concept that phytochemicals possess biological activities that promote glucose regulation, antioxidant defense, and diuresis, the study employed a Completely Randomized Design using female Swiss albino mice assigned to treatment and control groups. Ethanolic extracts of P. martellii at doses of 100, 200, and 400 mg/kg were evaluated through qualitative phytochemical screening, acute oral toxicity testing, diuretic assays, and antihyperglycemic assessment using standard laboratory procedures. Data were analyzed using mean values, three-way Analysis of Variance (ANOVA), and Tukey’s Honestly Significant Difference (HSD) test. The results confirmed the presence of alkaloids, flavonoids, saponins, glycosides, tannins, phenols, and other bioactive compounds. Acute oral toxicity testing demonstrated no mortality or severe toxic effects at 2000 mg/kg, indicating a favorable safety profile. The root extract exhibited the strongest diuretic activity, while the leaf extract at 100 mg/kg produced the greatest antihyperglycemic effect. Statistical analysis showed significant treatment effects on blood glucose levels, whereas diuretic responses among plant parts and dosage levels were generally comparable despite significant time-dependent changes. The findings demonstrate that P. martellii possesses promising diuretic and antihyperglycemic properties and may serve as a potential natural therapeutic alternative for managing diabetes and hypertension. Further studies are recommended to isolate the active compounds, investigate their mechanisms of action, evaluate chronic toxicity, optimize dosage, conduct clinical trials, and develop standardized pharmaceutical formulations. This study supports Sustainable Development Goal (SDG) 3: Good Health and Well-Being by exploring a potential plant-based therapeutic alternative for chronic diseases and SDG 9: Industry, Innovation and Infrastructure by providing scientific evidence that may contribute to the development of natural therapeutic products. The findings also promote public health and pharmaceutical sustainability by expanding scientific knowledge on indigenous medicinal plants and supporting future drug discovery and pharmacological research.